Edinburgh 2003 : closing the gap or enforcing the divisions? The 15th CCEM 27-30 October 2003 - Jobbins, David (2004)
Reports on deliberations at the 15th Conference of Commonwealth Education Ministers. Looks at issues such as the systematic poaching of teachers by developed nations and the Commonwealth's status on the inclusion of education within the World Trade Organization General Agreement on Trade in Services.